Build a React Application Using AWS Amplify. - McLaughlin, Brett (linkedin.com, 2020)
Leverage AWS Amplify to quickly build React apps using native AWS features. Discover how to reduce repetitive setup tasks, integrate your apps with AWS cloud services, and more.